Quantitative assessment of airway remodelling and response to allergen in asthma. Issue 11 (7th March 2019) - Adams, David C.; Miller, Alyssa J.; Applegate, Matthew B.; Cho, Josalyn L.; Hamilos, Daniel L.; Chee, Alex; Holz, Jasmin A.; Szabari, Margit V.; Hariri, Lida P.; Harris, R. Scott; Griffith, Jason W.; Luster, Andrew D.; et al.
ABSTRACT: Background and objective: In vivo evaluation of the microstructural differences between asthmatic and non‐asthmatic airways and their functional consequences is relevant to understanding and, potentially, treating asthma. In this study, we use endobronchial optical coherence tomography to investigate how allergic airways with asthma differ from allergic non‐asthmatic airways in baseline microstructure and in response to allergen challenge. Methods: A total of 45 subjects completed the study, including 20 allergic, mildly asthmatic individuals, 22 non‐asthmatic allergic controls and 3 healthy controls. A 3‐cm airway segment in the right middle and right upper lobe were imaged in each subject immediately before and 24 h following segmental allergen challenge to the right middle lobe. Relationships between optical airway measurements (epithelial and mucosal thicknesses, mucosal buckling and mucus) and airway obstruction (FEV1 /FVC (forced expiratory volume in 1 s/forced vital capacity) and FEV1 % (FEV1 as a percentage of predictive value)) were investigated. Results: Significant increases at baseline and in response to allergen were observed for all four of our imaging metrics in the asthmatic airways compared to the non‐asthmatic airways. Epithelial thickness and mucosal buckling exhibited a significant relationship to FEV1 /FVC in the asthmatic group. Conclusion: Simultaneous assessments of airway microstructure, buckling and mucus revealed both structural and functional differences between the mildly asthmatic and control groups, with airway buckling seeming to be the most relevant factor. The results of this study demonstrate that a comprehensive, microstructural approach to assessing the airways may be important in future asthma studies as well as in the monitoring and treatment of asthma. Abstract : Endobronchial optical coherence tomography is used to investigate the microstructural features of airway in allergic individuals with and without asthma, before and after allergen challenge. Quantification of these features reveals significant differences between the asthmatic and non‐asthmatic airways both at baseline and in response to allergen. See related Editorial